Supermarket healthy : recipes and know-how for eating well without spending a lot - D'Arabian, Melissa; Pelzel, Raquel (Clarkson Potter/Publishers, 2014)
"Food Network personality Melissa d'Arabian shows you how to make healthy meals for your whole family and still save lots of money and time, in a cookbook with 120 new dishes. If you think that eating healthier is too expensive, Melissa is here to guide you and prove that healthy eating can be easy, affordable, and achievable with everyday supermarket ingredients. She provides nutritional information with each recipe to help readers decide what recipes are best for them and what they're feeding their families. If the secret to better health is better cooking at home, then Melissa's book is the ultimate toolkit for every home cook who wants to eat healthier and save money"--